Physical properties and hydration evolution of dispersant containing calcium aluminate cement compositions for endodontic applications - A. P. Luz (Cerâmica, 2014)
The purpose of this study was to evaluate the physical properties and hydration evolution of calcium aluminate cement (CAC) compositions containing an advanced dispersant. The compressive strength, dimensional change, apparent porosity and quantitative X ray diffraction analysis (XRD) of the cement pastes were carried out over 1-15 days of curing (with the samples immersed in distilled water) at 37 ºC. The addition of a polymeric dispersant to the selected CAC (Secar 71) resulted in higher, but suitable expansion of the cement samples, and improved uniaxial compressive strength reaching values in the range of 73-87 MPa after 15 days. Quantitative XRD results also showed that C3AH6 and Al(OH)3 were the main phases detected during the cement hydration process, but CAH10 and C2AH8 were also found due to the higher water availability in the curing environment. According to the attained results, it could be concluded that the dispersant containing calcium aluminate cement compositions have the potential to be used as endodontic materials.